(untitled) (Research, Society and Development, 2022)
Objective: To develop the Hemomonitor software module with an alert system for monitoring patients using blood components. Methodology: This is an applied research carried out in a University Hospital, whose methodological trajectory followed three steps: 1) Characterization of the transfusion process at the study site; 2) Update on available software on the subject through a literature review; 3) Development of updated software based on specialized literature. Results: The flows of activities performed were triggered from the extraction of multivariate data from the systems, AGHUx and +Exames, used by the institution, to transform them into information. In addition, aiming at its operation, it was necessary to parameterize the alterations of the laboratory tests, to certify the HC prescription with the signature of the doctor responsible for the patient, to build a HC request sequencing, to allow the sharing of information and interface between the sectors, to standardize the supporting exams upon suspicion of transfusion, identify the patient’s sample and the HC bag in an appropriate way with the legislation, parameterize the reports for the compatibility tests, allow traceability, parameterize changes in vital signs to establish a temporal link, define the audit trails, train teams in terms of speed of processes, efficiency and substantial use of resources. Conclusion: The implementation of the Hemomonitor module and its application in a pilot unit made it possible to observe that its use can improve the real-time monitoring and follow-up of patients using HC, helping to anticipate effective measures to mitigate TR.